Another University is Possible - Barrantes Montero, Luis Guillermo (2013)
This paper proposes a way to be a University and to work as a University based on a new paradigm that responds to the demands of the 21st century society. After a brief overview of the traditional university models –as a way to illustrate, diachronically, the state of the situation of universities up to the currently prevailing model– a paradigm that is still in process is proposed: the transition from uni-versity to multi-diversity, through the integration of knowledge, development of critical thinking, and democratization of knowledge in order to reach common good